2021
DOI: 10.1155/2021/9024919
|View full text |Cite|
|
Sign up to set email alerts
|

Observation on the Efficacy of Shouhui Tongbian Capsule in the Treatment of Functional Constipation and Study on Its Regulatory Effect on Intestinal Flora

Abstract: Functional constipation is relatively common in both adults and children, exhibiting similar symptoms. However, there are significant differences in the epidemiology, symptomatology, pathophysiology, diagnostic tests, and treatment management of functional constipation by age. The treatment of functional constipation is generally based on lifestyle interventions, pelvic floor interventions, and pharmacotherapy. Pharmacological treatment is popular as the most direct and effective modality, especially the herba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It was found that effectiveness and quality of life of patients were significantly improved after prolonging the duration of SHTB. Furthermore, SHTB could regulate intestinal flora, and the regulating effect was more obvious in patients with shorter disease duration ( Zhang, Han, Zhang, Tian, & Yu, 2021 ). Zhou et al selected 98 elderly patients with functional constipation, which were divided into a control group (taking lactulose oral solution) and an study group (adding SHTB on the basis of the control group) and continuous treated for 4 weeks, judged the efficacy of the two groups, and counted the recurrence after stopping the drug ( Zhou & Zhou, 2019 ).…”
Section: Shtb For Treatment Of Functional Constipationmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that effectiveness and quality of life of patients were significantly improved after prolonging the duration of SHTB. Furthermore, SHTB could regulate intestinal flora, and the regulating effect was more obvious in patients with shorter disease duration ( Zhang, Han, Zhang, Tian, & Yu, 2021 ). Zhou et al selected 98 elderly patients with functional constipation, which were divided into a control group (taking lactulose oral solution) and an study group (adding SHTB on the basis of the control group) and continuous treated for 4 weeks, judged the efficacy of the two groups, and counted the recurrence after stopping the drug ( Zhou & Zhou, 2019 ).…”
Section: Shtb For Treatment Of Functional Constipationmentioning
confidence: 99%
“…SHTB could improve constipation not only by promoting intestinal motility and intestinal fluid secretion, but also by regulating intestinal flora and enhancing the energy metabolism and promoting the proliferation of ICCs ( Bai et al, 2022 , Lin et al, 2022 , Zhang et al, 2021 ). In the regulation of intestinal flora, SHTB could increase the relative abundances of Lactobacillus and the ratio of Firmicutes to Bacteroides (F/B).…”
Section: Shtb For Treatment Of Functional Constipationmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, the prevalence of constipation is on the rise, and its development is related to a variety of factors, such as social factors, dietary structure, medication or psychological factors. Constipation not only causes discomfort in defecation, but also contributes to some common anorectal diseases such as anal fissure and hemorrhoids, and for patients with underlying diseases such as hypertension and heart disease, it can also aggravate these diseases, posing a great threat to the physical and mental health of patients [1] .Currently, Western medicine mainly uses laxatives to treat constipation, but laxatives cannot be applied for a long time, and they not only produce dependence on constipated patients, but also may cause adverse effects such as blackening of the large intestine [2] .It has been reported that constipation persists in 20-40% of patients after appropriate application of modern medications for laxatives [3] .With the continuous research of many scholars on the diagnosis and treatment of functional constipation, it has been found that compared with Western medicine, the treatment of constipation with Chinese herbal medicine has shown the unique advantages of low cost, safety and cost-effectiveness [4] ,Long-term application is possible. It has been shown that dysbiosis of the intestinal flora is an important part of the pathogenesis of functional constipation [5] .Therefore, the author explores several possible mechanisms of action of TCM in the treatment of constipation from the perspective of the development mechanism of intestinal flora affecting functional constipation, in order to provide a new perspective and reference basis for TCM treatment of constipation.…”
Section: Introductionmentioning
confidence: 99%